2007
DOI: 10.1080/10916460500528722
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Heat of Vaporization from the Heat of Vaporization at Normal Boiling Point

Abstract: A generalized enthalpy-temperature correlation for a group of liquid compounds has been developed to represent the data for a wide range of temperatures. Detailed analysis shows that the proposed correlation fits the experimental measurements of enthalpy of liquid with the calculated values with an overall absolute error of 3.7% for 79 data points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The following 3C model studied here is that proposed recently by Al-Shorachi and Hashim (A-SH): Δ h / Δ h b n = m ( 1 t ) λ Originally they fixed the values of the parameters as m = 45.129353, n = 1.06402, λ = 0.3913. We tried to reproduce their results, but found that the dimensions used for the enthalpy could possibly be incorrect, so that the values of these parameters should be taken with caution.…”
Section: Correlationsmentioning
confidence: 99%
See 4 more Smart Citations
“…The following 3C model studied here is that proposed recently by Al-Shorachi and Hashim (A-SH): Δ h / Δ h b n = m ( 1 t ) λ Originally they fixed the values of the parameters as m = 45.129353, n = 1.06402, λ = 0.3913. We tried to reproduce their results, but found that the dimensions used for the enthalpy could possibly be incorrect, so that the values of these parameters should be taken with caution.…”
Section: Correlationsmentioning
confidence: 99%
“…[10][11][12][13][14] Some of them include coefficients that must be calculated for each substance, [15][16][17][18][19][20][21][22][23][24] or the value of the enthalpy at a given temperature. [25][26][27][28][29][30][31][32][33][34] The choice of a specific equation depends on several factors, mainly, the available number of experimental data, the temperature range over which one wants to apply the correlation, and the set of substances chosen for testing the equation. These factors and the desired or expected accuracy of the predicted values will also determine the number of adjustable parameters or coefficients in the correlation under consideration.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations